Identification of novel thermostable ω-transaminase and its application for enzymatic synthesis of chiral amines at high temperature. Issue 73 (21st July 2016) - Mathew, Sam; Deepankumar, Kanagavel; Shin, Giyoung; Hong, Eun Young; Kim, Byung-Gee; Chung, Taeowan; Yun, Hyungdon
Abstract : A novel thermostable ω-transaminase from Thermomicrobium roseum showing broad substrate specificity and high enantioselectivity was identified, expressed and biochemically characterized and it could produce chiral amines at high temperature. Abstract : A novel thermostable ω-transaminase from Thermomicrobium roseum which showed broad substrate specificity and high enantioselectivity was identified, expressed and biochemically characterized. The advantage of this enzyme to remove volatile inhibitory by-products was demonstrated by performing asymmetric synthesis and kinetic resolution at high temperature.